Enjoyment and oral English proficiency in future teachers - Guerra Ayala, Margit Julia; Reynosa Navarro, Enaidy; Durand Gómez, Emma Lourdes; Florez Lucana, Apolinar; Chambi Catacora, Maria Amparo del Pilar; Vargas Onofre, Elizabeth; Cari Checa, Edith (Frontiers in Education, 2024)
This study analyzed the relationship between enjoyment and oral English proficiency in Peruvian future teachers. It previously validated a measurement instrument of enjoyment setting for future teachers who are learners of English as a Foreign Language (EFL) and then delved into understanding the role of enjoyment as a predictor of oral proficiency. The sample comprised 119 students from a State Higher School of Education in Peru, randomly selected from various careers and grouped according to English language competency levels ranging from A1 to B1+ based on a subscale inspired by the Common European Framework of Reference (CEFR). Students' oral proficiency was evaluated using a rubric covering five aspects, and enjoyment was assessed through a nine-question questionnaire. The results initially demonstrated a significant positive relationship (r = 0.900, p < 0.001) between enjoyment and oral proficiency in EFL. Secondly, a linear regression model determined that enjoyment was a highly significant predictor (β = 0.957, p < 0.001) of oral proficiency. These findings support the importance of enjoyment in developing oral proficiency as a reliable tool to predict oral proficiency in EFL in the context of EFL teacher education. This study highlighted a significant influence of enjoyment on oral proficiency in learning EFL to prospective teachers. Results analysis underscored the importance of enjoyment as a significant predictor of oral proficiency, suggesting that promoting enjoyment in the learning and teaching process can be an effective strategy to foster significant development of oral skills in English. These findings have significant implications for teacher education, emphasizing the need to integrate activities and psycho-pedagogical approaches that promote enjoyment in the English classroom. Furthermore, the proposed model was validated as a reliable tool to assess teachers' enjoyment of learning EFL. Understanding and nurturing enjoyment in learning English can significantly enhance the oral English proficiency of future teachers and, ultimately, contribute to a more robust command of the EFL.